A meta-review of standard polysomnography parameters in Rett Syndrome - Zhang, Xin-Yan; Spruyt, Karen (Frontiers in Neurology, 2022)
Rett Syndrome (RTT, OMIM 312750), as a unique rare neurodevelopmental disorder mostly affecting females, causes severe multi-disabilities including poor sleep. This meta-analysis systematically reviewed the polysomnographic (PSG) data of individuals with RTT on both sleep macrostructure and sleep respiratory indexes, and compared them to literature normative values. Studies were collected from PubMed, Web of Science, PsycINFO, Ebsco, Scopus, and Cochrane Library till 26 April 2022. Across 13 included studies, the 134 selected RTT cases were mostly females being MECP2 (n = 41) and CDKL5 (n = 4) positive. They were further stratified by Gene, Age and Clinical features. Findings of comparison with literature normative values suggested shorter total sleep time (TST) and sleep onset latency (SOL), twice as long wake after sleep onset (WASO) with lower sleep efficiency (SEI) in RTT, as well as increased non-rapid eye movement stage 3 (stage N3) and decreased rapid eye movement sleep. Based on limited data per stratifications, we found in RTT cases <5 years old lower stage N3, in RTT cases >5 years old less WASO and in the epileptic strata more WASO. However, meta-results generated from studies designed with comparison groups only showed lower stage N1 in RTT than healthy comparison, together with similar SEI and stage N3 to primary snoring subjects. For sleep respiratory indexes, severe disordered sleep breathing was confirmed across roughly all RTT strata. We are the first study to meta-analyze PSG data of RTT subjects, illustrating shorter TST and aberrant sleep staging in RTT that may vary with age or presence of epilepsy. Severe nocturnal hypoxemia with apneic events was also demonstrated. More studies are needed to explore and elucidate the pathophysiological mechanisms of these sleep findings in future.